Memperkuat Toleransi Dan Kerukunan Melalui Pengabdian: Upaya Promosi Moderasi Beragama Dalam Masyarakat Desa Sumber Katon, Kecamatan Seputih Mataram, Lampung - Choirul Salim; Lilis Renfiana; Nanda Pratama (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The aim of this service is to provide an understanding of Religious Moderation, as a cultural strategy for maintaining a peaceful, tolerant Indonesia and respecting religion, Religious moderation as a way of living in harmony, mutual respect, care and tolerance without having to cause conflict because of existing differences. This service was carried out in Sumber Katon village, Seputih Subdistrict, Surabaya, where there are 3 religions adhered to by the community, namely Islam, Catholicism and Hinduism, there are also 6 mosques, 10 surau and 1 Catholic church. The service is carried out using 2 methods, namely by presenting material and discussions held at SDN 1 Sumber Katon and the Participatory Action Research (PAR) method, a process where communities try to study problems scientifically in order to guide, improve and evaluate their decisions and actions. This method is used to build community awareness, strengthen community capabilities, and help the community to improve their lives in the Sumber Katon Village Community. The result of this activity is that the participants and the community have an awareness of the importance of moderation and mutual respect for religious communities.